Degradasi Rhodamin B dengan Katalis ZnO-Fe Menggunakan Metode Fotosonolisis - Wahyunita Wulandari; Hary Sanjaya; Yohandri Yohandri (Departemen Kimia FMIPA UNP, 2021)
Degradation of rhodamin B with ZnO-Fe impetus utilizing photosonolysis strategy has been finished with some variety. The objectives of this examination is to know impact of variety radiation times, groupings of doping Fe, and portrayal some spectrophotometer. The absorbance of tests when debasement was recognized by an UV-Visible spectrophotometer. The yield showed greatest season of irradation to degradate rhodamin B at 150 minutes, with the most rate debasement at any point is 91,19%. The occasions will used to figure out which the best fixation doping to degradate rhodamin B. For the variety of impetus fixation was acquired at ZnO-Fe 20% with a debasement level of 23,10%. Examination ZnO doping Fe utilizing UV-DRS(Diffuse Reflectance Spectroscopy) got the greatest band hole esteem is 3,24 eV.